2022
DOI: 10.2196/34278
|View full text |Cite
|
Sign up to set email alerts
|

User Perceptions of eHealth and mHealth Services Promoting Physical Activity and Healthy Diets: Systematic Review

Abstract: Background Physical activity and a diet that follows general recommendations can help to prevent noncommunicable diseases. However, most adults do not meet current recommended guidelines, and support for behavior change needs to be strengthened. There is growing evidence that shows the benefits of eHealth and mobile health (mHealth) services in promoting healthy habits; however, their long-term effectiveness is uncertain because of nonadherence. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 57 publications
2
20
0
Order By: Relevance
“…Overall, participants agreed that physical activity was effective in improving mental health. This was consistent with previous findings [12][13][14] that users needed research for individualized or tailored mHealth services. The following unique themes were also estimated: limited effects of non-leisure physical activity on mental health, lower priority on physical activity rather than sleep and rest, reluctance to share the data within the groups, and difficulties in wearing the devices to measure physical activity due to work rules.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Overall, participants agreed that physical activity was effective in improving mental health. This was consistent with previous findings [12][13][14] that users needed research for individualized or tailored mHealth services. The following unique themes were also estimated: limited effects of non-leisure physical activity on mental health, lower priority on physical activity rather than sleep and rest, reluctance to share the data within the groups, and difficulties in wearing the devices to measure physical activity due to work rules.…”
Section: Discussionsupporting
confidence: 92%
“…As recommended by previous findings, mHealth services for physical activity and mental should also focus on individualization, attraction, and ease of use. Compared with previous systematic reviews [12][13][14] , workers also needed mHealth services to be tailored and individualized. Their perception that messages should be changed according to their occupation might be the primary factor to be tailored, and it was supported by the previous finding that levels of physical activity vary by occupation 23) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, a recent review found that consumers see opportunities to use eHealth to promote physical activity and healthy dietary behaviors. However, the study elicited that several points need to be considered to optimize eHealth tools [ 42 ], which includes considering a logical and practical approach rather than pure theoretical principles [ 32 ].…”
Section: Discussionmentioning
confidence: 99%